Outcomes of BRCA pre-implantation genetic testing according to the parental mutation origin: a cohort study - Ilana Weizel; Tal Shavit; Yulia Shuli; Chana Adler Lazarovich; Rivka Halevi; Tal Ben Ari; Shira Yaacobi-Artzi; Yaakov Bentov; Baruch Feldman; Anat Hershko Klement (BMC, 2024)
Abstract Background The process of gamete formation and early embryonic development involves rapid DNA replication, chromosome segregation and cell division. These processes may be affected by mutations in the BRCA1/2 genes. The aim of this study was to evaluate BRCA mutation inheritance and its effect on early embryonic development according to the parental origin of the mutation. The study question was approached by analyzing in vitro fertilization cycles (IVF) that included pre-implantation testing (PGT-M) for a BRCA gene mutation. Methods This retrospective cohort study compared cycles of pre-implantation genetic testing for mutations (PGT-M) between male and female patients diagnosed with BRCA 1/2 mutations (cases), to a control group of two other mutations with dominant inheritance (myotonic dystrophy (MD) and polycystic kidney disease (PKD)). Results were compared according to mutation type and through a generalized linear model analysis. Results The cohort included 88 PGT-M cycles (47 BRCA and 41 non-BRCA) among 50 patients. Maternal and paternal ages at oocyte retrieval were comparable between groups. When tested per cycle, FSH dose, maximum estradiol level, oocytes retrieved, number of zygotes, and number of embryos available for biopsy and affected embryos, were not significantly different among mutation types. All together 444 embryos were biopsied: the rate of affected embryos was comparable between groups. Among BRCA patients, the proportion of affected embryos was similar between maternal and paternal mutation origin (p = 0.24). In a generalized linear model analysis, the relative oocyte yield in maternal BRCA patients was significantly lower (0.7, as related to the non BRCA group)(p < 0.001). Zygote formation and blastulation were not affected by the BRCA gene among paternal cases (P = 0.176 and P = 0.293 respectively), nor by paternal versus maternal BRCA carriage (P = 0.904 and P = 0.149, respectively). Conclusions BRCA PGT-M cycles performed similarly compared to non-BRCA cycles. Inheritance rate and cycle parameters were not affected by the parental origin of the mutation.